Fear of cancer recurrence in South Korean survivors of breast cancer who have received adjuvant endocrine therapy: a cross-sectional study - Park, Seul Ki; Min, Yul Ha (Frontiers in Psychology, 2023)
Introduction: Fear of cancer recurrence (FCR) is one of the most-prevalent psychological problems among cancer survivors, and younger females who have received endocrine therapy are particularly at risk of high FCR. The aim of this study was to determine the relationship between high FCR and factors related to it in South Korean patients with breast cancer who receive adjuvant endocrine therapy (AET). Methods: This cross-sectional study recruited 326 patients with breast cancer who had received AET. All participants were asked to complete a personal information sheet, the short form of the Fear of Progression Questionnaire, and the Menopause Rating Scale. The factors associated with high FCR were analyzed using association-rule analysis. Results: The mean FCR score was 32.24 (SD = 10.22), and 137 of the 326 (42.0%) patients had high scores (≥34). Hot flushes and sweating (moderate to extremely severe), depressed mood (moderate to extremely severe), irritability (moderate to extremely severe), invasive stage, taking tamoxifen, and being married were associated with high FCR. Conclusion: Since FCR was common in patients with breast cancer who received AET, patients at a greater risk of experiencing FCR must be screened and supported.